1994
DOI: 10.1902/jop.1994.65.5.387
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Root Conditioning With Minocycline HCl in Removing Endotoxin From the Roots of Periodontally‐Involved Teeth

Abstract: Noting the acid-conditioning effect of minocycline on the root surface, we investigated the ability of minocycline to remove endotoxin on untreated, diseased cementum in vitro. Root surface specimens affected by periodontal disease were immersed in minocycline solution (10 mg/ml, 50 micrograms/ml, and 5 micrograms/ml) for 10 minutes, 1 day, 3 days, and 7 days, and endotoxin eluted was determined by the limulus amoebocyte lysate (LAL) assay. Specimens serving as controls were treated by immersion in pyrogen-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 18 publications
0
24
1
4
Order By: Relevance
“…Additionally, TAP and DAP application for three months caused significant reduction in root resistance to fracture [26]. The ability of minocycline, one of the antibiotics in TAP, to chelate calcium and demineralize dental hard tissues [28,29] might explain the significantly higher indentation parameters reported among TAP-treated dentine compared to DAPtreated dentine. However, the demineralization effect of TAP and DAP might play a significant role in endodontic regeneration by enhancing the attachment and growth of host stem cells on root canal surfaces through the exposure of embedded collagen fibers and mobilization of various growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, TAP and DAP application for three months caused significant reduction in root resistance to fracture [26]. The ability of minocycline, one of the antibiotics in TAP, to chelate calcium and demineralize dental hard tissues [28,29] might explain the significantly higher indentation parameters reported among TAP-treated dentine compared to DAPtreated dentine. However, the demineralization effect of TAP and DAP might play a significant role in endodontic regeneration by enhancing the attachment and growth of host stem cells on root canal surfaces through the exposure of embedded collagen fibers and mobilization of various growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…The present study also showed that 1 g/mL TAP treatment caused significantly higher reduction in microhardness at 500 µm from the pulp-dentine interface when compared to MTAP treatment at the same concentration. This could be explained by the ability of the minocycline present in TAP to chelate calcium and demineralize radicular dentine (22). It is also noteworthy that calcium hydroxide has been used as an intracanal medicament during endodontic regeneration procedures and was found to have negative effects on various mechanical properties of radicular dentine (23).…”
Section: E a F B G H C Dmentioning
confidence: 99%
“…Also, when the titanium was fabricated to have open pores or was threaded, the bone grows into the pores and irregularities of the metal (Seltzer et al, 1976). Root surfaces were conditioned with tetracycline, as it removes the smear layer and endotoxin from contaminated root surfaces (Minabe et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The excess cement was removed and a radiograph was taken to confirm the position ( Figure 4B). The root was treated with tetracycline (Minabe et al, 1994). The Figure 4C).…”
Section: Casementioning
confidence: 99%